Software Enabling School Improvement Through Analysis - Rouse, Sharon E.; Jones, Rose; Cleveland, Jonnie (Journal of the American Academy of Special Education Professionals, 2023)
This study is on data-gathering software for special teachers in local education agencies Grades K-14. Increasing pressure for the use of accountability to follow the effectiveness of meeting educational standards has caused schools to reassess methods of using data and the core technologies surrounding its collection. The amount of data collection mandated by the administration and government requirements frustrates special education teachers. The researchers sought to determine if in-service and preservice teachers would use a software platform for completing a required task, such as creating and sharing lesson plans. The results indicated that most in- and preservice teachers would use a software platform for achieving a required task when given the opportunity.